Estimating the Share of Sickness Absence Costs in Europe’s GDP – A Country, Gender and Time Perspective - Miszczyńska, Katarzyna M.; Antczak, Elżbieta; Prevolnik Rupel, Valentina (Journal of Finance and Financial Law, 2023)
The purpose of the article. The aim of the study was to calculate and evaluate the costs of employee sickness absence in European countries over the period 2006–2020. An additional objective was to analyse the sensitivity of the development of absenteeism costs depending on the changing level of the discount rate used in economic evaluation analyses. Methodology. The estimation and subsequent assessment of absenteeism of working-age people costs was based on human-capital approach and was carried out retrospectively using the morbidity, top-down approach, based on aggregated epidemiological data. As a measure of production loss volume, GDP per working person was adopted. Results of the research. The study indicated that there is variation in the cost of sickness absence across European countries, but no clustering relationship was identified from a geographic perspective. In addition, SACS is in the range of 1,9% – 2,1% in all countries in 2006 prices.